Classification of Additives for Organic Photovoltaic Devices. Issue 6 (21st January 2015) - Machui, Florian; Maisch, Philipp; Burgués‐Ceballos, Ignasi; Langner, Stefan; Krantz, Johannes; Ameri, Tayebeh; Brabec, Christoph J.
Abstract: The use of additives to improve the performance of organic photovoltaic cells has been intensely researched in recent years. However, so far, no system has been reported for the classification of additives and their functions. In this report, a system for classifying additives according to the fundamental mechanism by which they influence microstructure formation for P3HT:PCBM is suggested. The major parameters used for their classification are solubility and drying kinetics. Both are discussed in detail and their consequences on processing are analyzed. Furthermore, a general mechanism to classify the impact of additives on structure formation is suggested and discussed for different materials relevant to organic photovoltaic devices. Abstract : Top of the class: A system for classifying additives for processing organic photovoltaic devices according to the fundamental mechanism by which they influence microstructure formation from solution is suggested. The major parameters used for their classification are solubility and drying kinetics. Both are discussed in detail, the consequences on processing are analyzed and a general mechanism to classify the impact of additives on the structure formation is suggested.